The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1038/s41598-023-27795-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community structure of electrogenic biofilm developed on modified graphite anode in microbial fuel cell

Abstract: Formation of electrogenic microbial biofilm on the electrode is critical for harvesting electrical power from wastewater in microbial biofuel cells (MFCs). Although the knowledge of bacterial community structures in the biofilm is vital for the rational design of MFC electrodes, an in-depth study on the subject is still awaiting. Herein, we attempt to address this issue by creating electrogenic biofilm on modified graphite anodes assembled in an air–cathode MFC. The modification was performed with reduced grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…Such an aggregated biolm could produce abundant electrons by decomposing organic matter. 33 The nanowire-like structure was also observed between cells in the P-MFC (Fig. 6c and S3 †).…”
Section: Biolm Development On the Anode Surface And Electrochemical ...mentioning
confidence: 73%
See 1 more Smart Citation
“…Such an aggregated biolm could produce abundant electrons by decomposing organic matter. 33 The nanowire-like structure was also observed between cells in the P-MFC (Fig. 6c and S3 †).…”
Section: Biolm Development On the Anode Surface And Electrochemical ...mentioning
confidence: 73%
“…Previous studies reported that Acinetobacter using H 2 as an electron donor was predominant in the MFC. 33 In the electrode-attached cells (EAC), Geobacter (17.09%) was the most abundant classication, followed by Pseudomonas (16.25%) and Methanothrix (8.82%), all of which can decompose acetate to CH 4 and CO 2 under anaerobic conditions. 34 The NGS results revealed different microbial communities of P-and D-MFC, even though they were inoculated with the same inoculum at the start-up.…”
Section: Enrichment Of the Anodic Microbial Community In P-mfc And D-mfcmentioning
confidence: 99%
“…31 Taken together, the examples above illustrate how physical properties of the biofilm matrix play important roles in determining their functions, now a rapidly expanding area of biofilm research. Apart from the biophysical processes discussed here, other physical properties such as ecomechanics 2 and electrogenic 32 properties also play a role in shaping different biofilms. We assert that a thorough understanding of the role of physics in determining the emergent properties and functions of the matrix will yield a comprehensive understanding of biofilm formation, growth, and homeostasis.…”
Section: Gelation Of the Matrix Biopolymersmentioning
confidence: 99%
“…As the direction of electron transfer differs between these two reactions (in EET, electrons are transferred across the outer membrane, while in electron conduction, electrons are transferred lateral to the outer membrane), the molecular mechanisms underlying the two processes are different. 3−5 As bacteria create a three-dimensional architecture in BESs as well as in natural environments, 6 electron transfer along the cells directly contributes to the power output in these BESs, possibly with a larger impact than that of EET. 7 Thus, enhancing electron conduction along the cells can improve the power output of BESs, 8,9 highlighting the importance of molecular-level elucidation of electron conduction along bacterial cells for the development of highly efficient BESs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the electrochemical approach is effective for studying electron transfer between bacteria and electrodes, thereby providing insights into the molecular mechanisms of EET and presenting major implications for the development of energy and environmental technologies termed bioelectrochemical systems (BESs), such as microbial fuel cells and microbial electrosynthesis. , However, the existing understanding of the mechanisms underlying electron transfer reactions across multiple bacterial cells (electron conduction) is limited. As the direction of electron transfer differs between these two reactions (in EET, electrons are transferred across the outer membrane, while in electron conduction, electrons are transferred lateral to the outer membrane), the molecular mechanisms underlying the two processes are different. As bacteria create a three-dimensional architecture in BESs as well as in natural environments, electron transfer along the cells directly contributes to the power output in these BESs, possibly with a larger impact than that of EET . Thus, enhancing electron conduction along the cells can improve the power output of BESs, , highlighting the importance of molecular-level elucidation of electron conduction along bacterial cells for the development of highly efficient BESs.…”
Section: Introductionmentioning
confidence: 99%